Religious Identifications in Late Antique Papyri 3rd-12th Century Egypt - Brand, Mattias; Scheerlinck, Eline (Taylor & Francis, 2023)
This volume provides novel social-scientific and historical approaches to religious identifications in late antique (3rd-12th century) Egyptian papyri, bridging the gap between two academic fields that have been infrequently in full conversation: papyrology and the study of religion. Through eleven in-depth case studies of Christian, Islamic, "pagan," Jewish, Manichaean, and Hermetic texts and objects, this book offers new interpretations on markers of religious identity in papyrus documents written in Coptic, Greek, Hebrew, Aramaic, and Arabic. Using papyri as a window into the lives of ordinary believers, it explores their religious behavior and choices in everyday life. Three valuable perspectives are outlined and explored in these documents: a critical reflection on the concept of identity and the role of religious groups, a situational reading of religious repertoire and symbols, and a focus on speech acts as performative and efficacious utterances. Religious Identifications in Late Antique Papyri offers a wide scope and comparative approach to this topic, suitable for students and scholars of late antiquity and Egypt, as well as those interested in late antique religion. A PDF version of this book is available for free in Open Access at www.taylorfrancis.com. It has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.